2019
DOI: 10.1016/j.electacta.2019.03.126
|View full text |Cite
|
Sign up to set email alerts
|

Electrical reduction of perovskite electrodes for accelerating exsolution of nanoparticles

Abstract: Growth of finely dispersed nanocatalysts by exsolution of metal nanoparticles from perovskite oxides under reducing conditions at elevated temperature is a promising approach of producing highly active catalytic materials. An alternative method of exsolution using an applied potential has been recently shown to potentially accelerate the exsolution process of nanoparticles that can be achieved in minutes rather than the hours required in chemical reduction. In the present study, we investigate exsolution of na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 23 publications
1
29
0
Order By: Relevance
“…It was also shown that the nanoparticle ex-solution in electrochemical cells can be reached by the application of an electrical potential. 120 Specifically, metallic nanoparticles of size 30−100 nm were obtained from La 0.43 Ca 0.37 Ni 0.06 Ti 0.94 O 3 (LCTNi) and La 0.43 Ca 0.37 Ni 0.03 Fe 0.03 Ti 0.94 O 3 (LCTNi-Fe) perovskite phases in a carbon dioxide environment at the reduction potential over 2 V. As can be seen in Figure 14, such cells have shown 121 The XRD results have shown that the chemical composition of the obtained nanoparticles is Fe 0.64 Ni 0.36 . In addition, some La 2 O 3 was formed, which is undesirable due to its low activity.…”
Section: Electrochemical Performance Of Lafeo 3 Perovskitesmentioning
confidence: 99%
“…It was also shown that the nanoparticle ex-solution in electrochemical cells can be reached by the application of an electrical potential. 120 Specifically, metallic nanoparticles of size 30−100 nm were obtained from La 0.43 Ca 0.37 Ni 0.06 Ti 0.94 O 3 (LCTNi) and La 0.43 Ca 0.37 Ni 0.03 Fe 0.03 Ti 0.94 O 3 (LCTNi-Fe) perovskite phases in a carbon dioxide environment at the reduction potential over 2 V. As can be seen in Figure 14, such cells have shown 121 The XRD results have shown that the chemical composition of the obtained nanoparticles is Fe 0.64 Ni 0.36 . In addition, some La 2 O 3 was formed, which is undesirable due to its low activity.…”
Section: Electrochemical Performance Of Lafeo 3 Perovskitesmentioning
confidence: 99%
“…22 The NPs not only provide active sites for CO 2 /CO adsorption but also increase the catalytically active surface area. 23,24 In situ NP exsolution has been demonstrated in a variety of perovskite systems, such as La 0.52 Sr 0.28 Ni 0.06 Ti 0.94 -O 3 , 21 La 0.43 Ca 0.37 Ni 0.03 Fe 0.03 Ti 0.94 O 3Àg , 25 24 and, Pr 0.5 Ba 0.5 Mn 0.9 Co 0.1 O 3 , 28 to name a few.…”
Section: Introductionmentioning
confidence: 99%
“…Redox exsolution, an alternative to assembly and deposition methods, has the potential to produce supported metal nanoparticles with combined high activity and stability. In this method, active species are substituted in a perovskite oxide matrix and subsequently emerge as metal nanoparticles at the surface, normally driven by thermal [3] or electrical reduction [4] . Exsolved nanoparticles are epitaxially grown from the parent oxide and partially socketed in it.…”
Section: Introductionmentioning
confidence: 99%